Optimizing Social Media as a Promotional Tool to Attract Consumers to Warung Bakso - Muammar Rinaldi; Tina Muhardika Handayani; Debi Masri (Outline Publisher, 2025)
In the digital era, social media plays a crucial role in product promotion, especially in the culinary sector such as meatball stalls. This activity aims to optimize the use of social media as a promotional tool for meatball shop owners through training and mentoring. The activity method consists of observation, in-depth interviews, and social media content analysis. The service results show a significant increase in stall owners' knowledge of digital marketing strategies, which is reflected in their ability to create interesting content and better interactions with consumers. Implementing social media strategies also results in significant increases in consumer engagement and sales turnover, as well as customer loyalty. These findings show that social media training not only improves the competency of stall owners, but also contributes to the growth of small businesses, encouraging sustainability and competitiveness in an increasingly competitive market.